An overview of nematodes infecting urban and wild rats (Muridae) in Malaysia - M. Sithambaram, Paramasvaran; Abdullah Sani, Rehana; Krishnasamy, M.; Mustafa, Amal Nasir; Hassan, Latiffah; Mohd Zain, Siti Nursheena; Jeffery, John; Louis Masalamany, A. S. Santhana Raj; Ibrahim, Latifah; Abdul Aziz,; Subramaniam, Vellayan; Sengol, Selvanesan (Department of Veterinary Services Malaysia, 2012)
Rodents particularly those belonging to the Muridae family in Malaysia have been well studied because of their medical and economic importance. Much of the work on rodents has been focusing on the identification of endo and ecto parasites. Parasites in rats (Murids) particularly helminthes belonging to the Nematoda family have been described by many workers for more than a century. This paper is an attempt to compile 50 papers on rodent nematodes that has been published in various scientific journals over the last 100 years in Malaysia. It is hoped that this literature overview on rodent nematodes will come useful as a reference material for the budding parasitologist and biology scientist.